2006
DOI: 10.1094/php-2006-1016-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Detection Techniques Used in US Regulatory Programs to Determine Presence of Phytophthora ramorum in Camellia japonica ‘Nucio's Gem’ in an Infested Nursery in Southern California

Abstract: Phytophthora ramorum (Pram) is a pathogen of regulatory concern in the USA, and accurate diagnostics is a key component in the response to potential pathogen outbreaks. Although the molecular diagnostic protocols used in regulatory programs have been evaluated using regulatory samples, to date, no direct comparison of these methods has been analyzed within a nursery setting. A block of 300 camellia plants within a California nursery known to be infested with Pram was simultaneously assayed for visual symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Seedlings were hand-planted; in mulch treatments, seedlings were placed with the crowns above the soil line to encourage root growth within the mulch. However, studies with P. ramorum in leaf tissue showed a false negative rate of 29% for this ELISA test kit and 56% for culturing, as compared with detection using nested PCR (12), indicating that a 91% recovery rate may be taken as acceptable confirmation of Phytophthora infection in the symptomatic plants. Chemical mowing (low rates of glyphosate) was used for weed control, with some addifional mowing and handweeding performed during plot assessments.…”
Section: Methodsmentioning
confidence: 89%
“…Seedlings were hand-planted; in mulch treatments, seedlings were placed with the crowns above the soil line to encourage root growth within the mulch. However, studies with P. ramorum in leaf tissue showed a false negative rate of 29% for this ELISA test kit and 56% for culturing, as compared with detection using nested PCR (12), indicating that a 91% recovery rate may be taken as acceptable confirmation of Phytophthora infection in the symptomatic plants. Chemical mowing (low rates of glyphosate) was used for weed control, with some addifional mowing and handweeding performed during plot assessments.…”
Section: Methodsmentioning
confidence: 89%
“…This result may be due to coalescing foci, as suggested by a comparative analysis of different detection techniques (above-and below-ground ELISA, real-time-PCR, nested PCR and culture) in a P. ramorum-infested nursery growing Camellia japonica in California (Bulluck et al, 2006).…”
Section: Prevention Of Infestation Of the Commoditymentioning
confidence: 99%
“…Although a preliminary study from California suggests a spread in nurseries that is within the range of what is imposed by regulations (Tjosvold, 2010), Heungens et al (2010) reported no clear pattern of focal spread, as the same genotype was detected at more than 10 m distances in a genetic study over 2 growing seasons at a large commercial nursery in Belgium with multiple infestations of P. ramorum. This result may be due to coalescing foci, as suggested by a comparative analysis of different detection techniques (above-and below-ground ELISA, real-time-PCR, nested PCR and culture) in a P. ramorum-infested nursery growing Camellia japonica in California (Bulluck et al, 2006).…”
Section: • Prevention Of Infestation Of the Commoditymentioning
confidence: 99%
“…These diseases can be difficult or impossible to distinguish by symptoms alone and in-lab diagnostic testing is required for accurate pathogen identification. Identification of ambiguous Phytophthora species has traditionally relied on techniques such as baiting, isolation onto a Phytophthora semi-selective medium, DNA extraction and polymerase chain reaction (PCR) or antibodies (i.e., immunostrips) to identify the genus or species present [5][6][7][8]. However, this is time consuming and some species, such as the causal agent of sudden oak death, Phytophthora ramorum [9], are of regulatory importance, requiring a rapid and accurate identification.…”
Section: Introductionmentioning
confidence: 99%